2001
DOI: 10.1034/j.1600-6143.2001.001002162.x
|View full text |Cite
|
Sign up to set email alerts
|

Donor Scoring System for Cadaveric Renal Transplantation

Abstract: We studied early renal function in 241 consecutive patients who received cadaveric renal transplants at two different transplantation centers (group 1, n = 90; group 2, n = 151). Univariate and multivariate analyses of data from group 1 showed a significant correlation between seven donor variables and early renal function after cadaveric renal transplantation. A scoring system was developed from these seven donor variables (cause of death, 0-6 points; history of hypertension, 0-6; final creatinine clearance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 11 publications
2
50
0
1
Order By: Relevance
“…The mean and median ECD relative risk of the kidneys in our group was modest at 1.24 -0.29 and 1.14 ( Table 6); only nine kidneys (6.8%) met the definition of an ECD kidney. Similarly, the mean and median Novartis, Sangstat, and Nyberg scores for the transplants in our study are all quite modest ( (20), which they defined as the need for more than one hemodialysis treatment within 30 days of transplantation. Table 7 shows the outcome of Cox proportional hazards analysis of time to graft function using univariate models.…”
Section: Baseline Characteristicssupporting
confidence: 55%
See 1 more Smart Citation
“…The mean and median ECD relative risk of the kidneys in our group was modest at 1.24 -0.29 and 1.14 ( Table 6); only nine kidneys (6.8%) met the definition of an ECD kidney. Similarly, the mean and median Novartis, Sangstat, and Nyberg scores for the transplants in our study are all quite modest ( (20), which they defined as the need for more than one hemodialysis treatment within 30 days of transplantation. Table 7 shows the outcome of Cox proportional hazards analysis of time to graft function using univariate models.…”
Section: Baseline Characteristicssupporting
confidence: 55%
“…Two of the indices, Sangstat (18) and Novartis (19), were derived to identify transplant recipients at high risk of DGF. Finally, the Nyberg (20) scoring system was derived to identify transplant recipients at high risk for early graft dysfunction. All four indices were retrospectively derived; two of the indices (Novartis and Nyberg) have been prospectively validated.…”
Section: Immunosuppression and Rejectionmentioning
confidence: 99%
“…We found that renal fibrosis scores were weakly associated with the final creatinine clearance, supporting its implementation in some donor scoring systems. 32 Interestingly, we found that fibrosis positively correlated with KIM-1 scores, suggesting increased susceptibility of kidneys with fibrosis to ischemic injury. Our findings are in accordance with previous animal studies demonstrating that focal KIM-1 expression correlated with interstitial fibrosis and proliferation 33 ; therefore, KIM-1 may play an important role in the restoration of the morphologic integrity and function of the kidney.…”
Section: Discussionmentioning
confidence: 62%
“…On the other hand, the binary nature of the ECD definition may have underappreciated the variability of the quality of the organ. On these grounds, (Nyberg et al, 2001) a more granulated scoring system (deceased donor score, DDS) was developed. DDS was based on seven different donor variables easily available at the moment of procurement.…”
Section: Ddsmentioning
confidence: 99%